The locus of tragedy - Cools, Arthur, 1967- (Studies in Contemporary Phenomenology, 2008)
Ask for the tragic and Europe will answer. Leaving behind the philosophers' enthusiasm of the nineteenth century, 'tragedy' and 'the tragic' now seem little more than vague containers. However, it appears that we still discover a tragic essence in our personal lives. Time and again tragedy is being registered, written down and staged. This book wants to open a contemporary philosophical perspective on the tragic. What is the locus of tragedy? Does it relate to metaphysics, the gods, destiny, and chance? Or is it a matter of ethics, of the Law and its transgression? Does man himself occupy the locus of tragedy, because of his unreasonable and boundless desires, as many philosophers have suggested? Is man today still able to account for his tragic condition? Or do we locate the tragic first and foremost in the esthetic imagination? Is not the theatrical genre of tragedy the locus authenticus of all things tragic? Is there more to the tragic than drama and play?